(untitled) (Research, Society and Development, 2020)
The forage cactus is one of the main forages used to feed ruminants in semiarid regions. Cladode area and weight measurements are necessary in agronomic studies, being one of the main parameters used to evaluate the cacti growth. Thus, the objective was to define the best models for estimating the cladode area and weight of Little Sweet clone (Nopalea cochenillifera) in a non-destructive way based on the cladod linear dimensions. To determine the cladode area and weight, 582 cladodes were randomly collected, with 191 primary, 186 secondary and 205 tertiary. Then, the cladodes were individually numbered and weighed. The linear dimensions of length (L), maximum width (W) and thickness (T) of each cladode were measured with a digital caliper. The cladode area was calculated using the gravimetric method. Linear regression, gamma and power models were used to explain the cladode area and weight. The evaluation criteria of the models were determination coefficient, Akaike information criterion, sum of squared residue and Willmott index. The power models were the most efficient to explain the area of ​​the cladode (AC) as a function of the product of the length by the width, and the weight of the cladode (WC) as a function of the product of the length by the width and thickness. The power models, =LW0.985 and =0,0045(T0,806 LW1,099), can be used with greater precision to estimate, respectively, the cladode area and weight of the Nopalea cochenillifera Little Sweet clone based on the values ​​of the linear dimensions of the cladode.